Intravenous Peramivir for Treatment of Influenza A and B Virus Infection in High-Risk Patients - Kohno, Shigeru (American Society for Microbiology, 2011)
Influenza virus infections are known to persist longer in patients with underlying diseases, including respiratory tract diseases, and tend to become complicated by secondary influenza-associated infections, such as pneumonia. To assess the efficacy and safety of the novel anti-influenza virus drug peramivir in high-risk patients, we conducted a clinical trial of patients with diabetes or chronic respiratory tract diseases and patients being treated with drugs that suppress immune function. In this multicenter, uncontrolled, randomized, double-blind study, peramivir was intravenously administered at 300 or 600 mg/day for 1 to 5 days, as needed. Efficacy was investigated in 37 patients (300 mg, n = 18 patients; 600 mg, n = 19 patients). The median durations of influenza illness were 68.6 h (90% confidence interval, 41.5 to 113.4 h) overall, 114.4 h (90% confidence interval, 40.2 to 235.3 h) in the 300-mg group, and 42.3 h (90% confidence interval, 30.0 to 82.7 h) in the 600-mg group. The hazard ratio for the 600-mg group compared to the 300-mg group was 0.497 (90% confidence interval, 0.251 to 0.984), and the duration of influenza illness was significantly shorter in the 600-mg group than in the 300-mg group. Among the 42 patients in the safety analysis set, adverse events occurred in 73.8% and adverse drug reactions in 33.3%. No adverse events were particularly problematic clinically, and all patients recovered quickly from all events. The measured blood drug concentrations showed no tendency toward accumulation. Drug accumulation with repeated doses was thus considered to be of little concern. Intravenous peramivir appears to offer a potentially useful treatment for high-risk patients in the future.